Successful in Sports but Worse in School? Adolescent Student-Athletes’ Development of Scholastic Performances - Niehues, Maike; Gerlach, Erin; Wendeborn, Thomas; Sallen, Jeffrey (Frontiers in Education, 2022)
Studies have evaluated the effectiveness of dual career (DC) support services among student-athletes by examining scholastic performances. These studies investigated self-reported grades student-athletes or focused on career choices student-athletes made after leaving school. Most of these studies examined scholastic performances cross-sectionally among lower secondary school students-athletes or student-athletes in higher education. The present longitudinal field study in a quasi-experimental design aims to evaluate the development of scholastic performances among upper secondary school students aged 16 to 19 by using standardised scholastic assessments and grade points in the subject English over a course of three to four years. A sample of 159 students (54.4% females) at three German Elite Sport Schools (ESS) and three comprehensive schools participated in the study. The sample was split into six groups according to three criteria: (1) students’ athletic engagement, (2) school type attendance, and (3) usage of DC support services in secondary school. Repeated-measurement analyses of variance were conducted in order to evaluate the impact of the three previously mentioned criteria as well as their interaction on the development of scholastic performances. Findings indicated that the development of English performance levels differ among the six groups.